Do Work-Family Conflict and Resiliency Mediate Police Stress and Burnout: a Study of State Police Officers - Griffin, Jennifer D. (American journal of criminal justice, 2018)
Occupational stress and burnout have long been recognized as common hazards among police officers. The present study examines whether demographic characteristics and assignment affect police officers’ work-family conflict (WFC), resiliency, stress and burnout, and whether WFC and resiliency mediate the stress and burnout of police officers. The data were collected from a Mid-Atlantic state police agency in the United States of America through a web-based survey. Regression results revealed that minority officers tended to have lower levels of WFC and burnout and better educated officers reported lower degrees of WFC and stress. WFC was positively related to stress and burnout, while resilience was inversely linked to stress and burnout. The effects of race and education disappeared when WFC and resiliency entered the regression, suggesting that their impact was largely mediated by WFC and resiliency. Lastly, stress was found to be positively associated with burnout. Implications for research and policy are discussed.